INSTITUIÇÕES DE ATENDIMENTO A TOXICODEPENDENTES: EXPERIÊNCIAS NO VALE DO PARAÍBA - Jesus, Claudia Fabiana de (2006)
Currently, an increase of offers and psychoactive substance search is verified, and observes an increase of institutions of assistance to this demand. The present researce approaches the attendance institutions the toxicodependentes in the Valley of the Paraíba, São Paulo, Brazil and has as objective to describe and to argue the method of attendance adopted for the institutions, from the approach of the responsible ones. It is used semi-directed interview, the used method is content analysis and is searched ten institutions. The presence of formerdependents in the team and the regimen of internment predominates. It is marcante the lack of professionals of the health area and of professionals with formation in chemical dependence and 60% of the institutions they are therapeutical communities. It prevails, as attendance method, the work, disciplines it and the espiritualidade. It does not have evaluation of results and the goal is the abstinence. It has little systematic control by means of the competent agencies and the institutions do not fulfill minimum requirements for its functioning. However, exactly with the financial difficulties, lack of resources as well as of qualified professionals, these institutions promote cares to put in a home, feeding, hygiene and adaptation to a routine. Given the complexity in the field of the drogadependência, it is suggested diversity of treatment and intervention options